Efek Analgetik Ekstrak Etanol Kelopak Rosella (Hibiscus sabdariffa L) Pada Mencit Jantan (Mus musculus) - Ridwan Baihaqi; M. Yulis Hamidy; Eka Bebasari (Fakultas Kedokteran Universitas Riau, 2014)
Indonesia has been known for its traditional medicine and one of the plants used for tradisional medicine is Hibiscussabdariffa L. The roselle (Hibiscus sabdariffa L) calyx has antipyretic effect by blocking prostaglandin synthesis. Thepurpose of this study was to find out the existences of analgesic effect of roselle (Hibiscus sabdariffa L) calyx ethanolextract. This experimental research used a post test only design that was conducted on 25 male mices weighting 20-35 g. The mices were divided into 5 treatment groups and given the CMC-Na 0,5% (negative control), asetosal 65 mg/kgBB (positive control) and groups of roselle (Hibiscus sabdariffa L) calyx ethanol extract dose of 200 mg/kgBB,400 mg/kgBB and 800 mg/kgBB. Pain stimulus was given chemically by using 1% acetic acid that injectedintraperitoneally 30 minutes after sample was given the extract, the response of the mices will be writhing. It calledpositive response if percentage potency of analgesic e” 50%. The result of this research showed that all dosage ofroselle (Hibiscus sabdariffa L) calyx ethanol extract had an analgesic effect.